Exact Evaluation of Statistical Moments in Superradiant Emission - Nakamura, Gilberto M.; Cabella, Brenno [UNESP]; Martinez, Alexandre S. [UNESP] (Mdpi, 2019)
Superradiance describes the coherent collective radiation caused by the interaction between many emitters, mediated by a shared electromagnetic field. Recent experiments involving Bose-Einstein condensates coupled to high-finesse cavities and interacting quantum dots in condensed-matter have attracted attention to the superradiant regime as a fundamental step to create quantum technologies. Here, we consider a simplified description of superradiance that allows the evaluation of statistical moments. A correspondence with the classical birthday problem recovers the statistical moments for discrete time and an arbitrary number of emitters. In addition, the correspondence provides a way to calculate the degeneracy of the problem.
Keywords: stochastic processes; complex systems; self-organization; Dicke model; birthday problem